Rare bird documentation form for Northern Goshawk at Big Marsh, 1984 - Moore, Francis L.et al (1984)
Rare bird documentation form for a Northern Goshawk at Big Marsh in Butler County, IA on March 24, 1984. Epson - sheet feed